Analisis Pendapatan Premi Dan Beban Klaim Terhadap Laporan Keuangan Perusahaan Asuransi - M, Annisha Uliana; Hasibuan, David HM (Institut Bisnis dan Informatika Kesatuan, 2014)
The purpose of this research is to investigate and analyse th effect premium income and claims expense, on financial statements. The data were collected by observations and thn analysed using comaparative and/or trend analysis. This analysis is used to identify the changes that occurred in the financial statements of the insurance company, as indications of presence of a premium increase or decrease revenue and claims expense in the amount of IDR or percentage in a certain period. The results showed that (1) premium income and expense claims in a period of increased and decreased, (2) increase or decrease in premium income was very influential on the insurance company's financial statements, (3) increase or decrease the burden of claims is very influential on the financial statements of insurance companies. Keywords : premium income, claims expense, financial statements of insurance companies